Immigration and Wage Dynamics in Germany - Klinger, Sabine (IMF Working Papers; Working Paper ;, 2019)
German wages have not increased very rapidly in the last decade despite strong employment growth and a 5 percentage point decline in the unemployment rate. Our analysis shows that a large part of the decline in unemployment was structural. Micro-founded Phillips curves fit the German data rather well and suggest that relatively low wage growth can be largely attributed to low inflation expectations and low productivity growth. There is no evidence - from either aggregate or micro-level administrative data - that large immigration flows since 2012 have had dampening effects on aggregate wage growth, as complementarity effects offset composition and competition effects.